The foundations of social research : meaning and perspective in the research process - Crotty, Michael. (Allen and Unwin, 1998)
Introduction: the research process. Positivism: the march of science. Constructionism: the making of meaning. Interpretivism: for and against culture. Interpretivism: the way of hermeneutics...